Background knowledge, attitude and practice of contraception among Pahang women - Husin, Roziah; Abdulwahab, Dalia F; Momamed, Norlidah; Mat Ali, Nor Huda; Ismail , Rozihan (2013)
Objectives: Women bear the highest stress and burden of reproductive health. It is the women’s right to choose and practice their own convenient contraceptive methods. Thus spreading of proper information regarding contraception is vital to reduce the reproductive related morbidity and mortality in our society. In our survey we aimed to study the awareness and the factors impacting knowledge regarding contraception among Pahang women. To find out regarding women attitude and perception of contraception